2013
DOI: 10.1007/jhep09(2013)123
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constant, near brane behavior and singularities

Abstract: We show that the classical cosmological constant in type II flux compactifications can be written as a sum of terms from the action of localized sources plus a specific contribution from non-trivial background fluxes. Exploiting two global scaling symmetries of the classical supergravity action, we find that the flux contribution can in many interesting cases be set to zero such that the cosmological constant is fully determined by the boundary conditions of the fields in the near-source region. This generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(155 citation statements)
references
References 59 publications
14
140
1
Order By: Relevance
“…This implies that the quadratic term in the polarization potential for this channel vanishes, 8 and hence we have:…”
Section: Jhep02(2015)146mentioning
confidence: 97%
See 1 more Smart Citation
“…This implies that the quadratic term in the polarization potential for this channel vanishes, 8 and hence we have:…”
Section: Jhep02(2015)146mentioning
confidence: 97%
“…This intuition was challenged by the fact that the supergravity solution describing backreacting anti-D3 branes in the Klebanov-Strassler solution must have a certain singularity in the infrared, both when the anti-D3 branes are smeared on the S 3 at the bottom of the deformed conifold [4][5][6][7], and also when they are localized [8]. Furthermore, it was shown that this singularity cannot be cloaked with a black hole horizon [9,10], nor via polarization into D5 branes at a finite distance away from the KS tip [11].…”
Section: Introductionmentioning
confidence: 99%
“…Related and extremely instructive results using probe branes in holographic set-ups have also appeared in the earlier literature [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Jhep08(2016)047mentioning
confidence: 62%
“…27,28 The gauge potential satisfies 17) where Ω M is the volume form of M , generalizing (3.7). 29 The ambiguity in C d , coming from the integration of (3.17), produces the usual ambiguity in the probe action. Since all brane worldvolumes we consider are homologous to each other, this ambiguity is simply an overall worldvolume-independent constant in the action.…”
Section: Jhep08(2016)047mentioning
confidence: 99%
See 1 more Smart Citation